Current treatment options for psoriatic arthritis: spotlight on abatacept - Ursini F; Russo E; De Giorgio R; De Sarro G; D'Angelo S (Dove Medical Press, 2018)
Francesco Ursini,1,2 Emilio Russo,1 Roberto De Giorgio,3 Giovambattista De Sarro,1 Salvatore D’Angelo4,5 1Department of Health Sciences, University of Catanzaro “Magna Graecia”, Catanzaro, Italy; 2Associazione Calabrese per la Ricerca in Reumatologia, Catanzaro, Italy; 3Department of Medical Sciences, University of Ferrara, Ferrara, Italy; 4Rheumatology Department of Lucania, Rheumatology Institute of Lucania (IReL), Potenza Italy; 5Basilicata Ricerca Biomedica (BRB), Potenza, Italy Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory disease of joints, tendon sheaths, and entheses affecting patients with established skin psoriasis, or, less frequently, patients without a personal history of psoriasis with a positive familial history. Many treatment options are now available to deal with the different aspects of the disease, including traditional and biological disease-modifying antirheumatic drugs and the recently released targeted synthetic disease-modifying antirheumatic drugs. However, ~40% of patients still fail to achieve a meaningful clinical response to first-line biologic therapy advocating the development of novel medications. It is now well accepted that T-cells participate in the immunopathogenesis of several autoimmune diseases. For this reason, the potential intervention on T-cells represented an attractive therapeutic target for a long time, becoming a clinical reality with the development of abatacept. Abatacept is a biologic agent selectively targeting the T-cell costimulatory signal delivered through the CD80/86-CD28 pathway and was approved in December 2005 by the US Food and Drug Administration and in May 2007 by European Medicines Agency for the treatment of patients with rheumatoid arthritis in combination with methotrexate. Based on the relevant role of T-cells in PsA pathogenesis and following the positive results obtained in a phase III clinical trial, abatacept recently received approval for treatment of patients with PsA. In this review, we will focus on the current knowledge about the emerging role of abatacept in treatment of PsA. Keywords: abatacept, CTLA4-Ig, T-cell, psoriatic arthritis, efficacy, safety